Human transitional and IgMlow mature naïve B cells preserve permissive B‐cell receptors. Issue 8 (4th June 2021) - Zhang, Zhiguo; Jara, Christopher J; Singh, Mandeep; Xu, Huji; Goodnow, Christopher C; Jackson, Katherine JL; Reed, Joanne H
Abstract: The level of immunoglobulin M (IgM) displayed on the surface of peripheral blood B cells exhibits a broad dynamic range and has been associated with both development and selection. To determine whether IgM surface expression associates with distinct immunoglobulin heavy‐chain (IGH) repertoire properties, we performed deep IgM sequencing of peripheral blood transitional and mature naïve B cells in the upper and lower quartiles of surface IgM expression for 12 healthy donors. Mature naïve B cells within the lowest quartile for surface IgM expression displayed more diverse IGH features including increased complementarity‐determining region 3 length, IGHJ6 segment usage and aromatic amino acids compared with mature naïve B cells with high surface IgM. There were no differences between IGH repertoires for transitional B cells with high or low surface IgM. These findings suggest that a selection checkpoint during progression of transitional to mature naïve B cells reduces the breadth of the IGH repertoire among high surface IgM B cells but that diversity is preserved in B cells expressing low levels of surface IgM. Abstract : Self‐tolerance mechanisms tend to remove antibodies with long complementarity‐determining region 3 sequences that are enriched in aromatic amino acids, which has the potential to create holes in the B‐cell repertoire, making us vulnerable to pathogens that mimic self. We reveal a population of circulating mature naïve B cells with low surface immunoglobulin M that preserve these permissive antibody properties in healthy people.